2008
DOI: 10.1364/oe.16.012987
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Kerr nonlinear properties of plasma-deposited silicon nitride/ silicon dioxide waveguides

Abstract: We introduce and present experimental evaluations of loss and nonlinear optical response in a waveguide and an optical resonator, both implemented with a silicon nitride/ silicon dioxide material platform prepared by plasma-enhanced chemical vapor deposition with dual frequency reactors that significantly reduce the stress and the consequent loss of the devices. We measure a relatively small loss of approximately 4dB/cm in the waveguides. The fabricated ring resonators in add-drop and all-pass arrangements dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
254
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 398 publications
(273 citation statements)
references
References 18 publications
14
254
2
3
Order By: Relevance
“…The first nonlinear optical studies of SiN waveguides were reported in 2008 [55] (Fig. 1a), showing nonlinear shifting of the resonances in 700 nm thick SiN ring resonators obtained with 200 mW CW optical pump power.…”
Section: Si 3 N 4 Nanowiresmentioning
confidence: 97%
See 3 more Smart Citations
“…The first nonlinear optical studies of SiN waveguides were reported in 2008 [55] (Fig. 1a), showing nonlinear shifting of the resonances in 700 nm thick SiN ring resonators obtained with 200 mW CW optical pump power.…”
Section: Si 3 N 4 Nanowiresmentioning
confidence: 97%
“…However, only recently [55] it has been proposed as a platform for nonlinear optics. Historically, the challenge for SiN optical devices has been to grow low loss layers thicker than 250 nm, due to tensile film stress.…”
Section: Si 3 N 4 Nanowiresmentioning
confidence: 99%
See 2 more Smart Citations
“…[30][31][32] Additionally, a range of hybrid photonic devices based on silicon nitride structures has been demonstrated. 10,[33][34][35][36][37] In contrast to pure silicon, the material does not display large intrinsic nonlinearities or a substantial free carrier absorption 38 and therefore allows us to observe the nonlinear response of the QDs without waveguide-induced background. A schematic of the sample is displayed in Fig.…”
Section: Samplesmentioning
confidence: 99%